Sustainable materials in the flexible packaging industry – an overview - Konstantinos Papageorgiou; Stamatina Theochari; Konstantinos Milioris (Polimery)
The article presents the latest solutions for sustainable flexible packaging materials, covering articles published in 2017–2022. Discussed, among others bio-based, biodegradable, and recycled poly-mers, and paper, which are slowly being adopted by the industry and are expected to replace traditional packaging materials from non-renewable sources in the coming years.